2023
DOI: 10.1002/cjce.24868
|View full text |Cite
|
Sign up to set email alerts
|

Thermoset/graphene polymer composites—A review of processing and properties

Abstract: Polymer‐carbon nanocomposites incorporate the exceptional properties of both the polymer matrices, such as low cost and simple processing, with the distinctive features of the carbon‐based fillers, such as high electrical and thermal conductivities, and excellent mechanical properties. Various fillers like carbon black (CB), graphite, expanded graphite (EG), and carbon nanotubes (CNTs) are being used to produce materials with advanced properties. However, at high filler loading, these filler materials have som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 105 publications
0
3
0
Order By: Relevance
“…The authors of the articles in this issue join us from many countries and institutions across the globe (Figure 1 and Table 1) to thank Archie for his enduring legacy in polymerization reaction engineering, a field of academic and industrial interest that he established practically single‐handedly. [ 1–45 ]…”
Section: Figurementioning
confidence: 99%
“…The authors of the articles in this issue join us from many countries and institutions across the globe (Figure 1 and Table 1) to thank Archie for his enduring legacy in polymerization reaction engineering, a field of academic and industrial interest that he established practically single‐handedly. [ 1–45 ]…”
Section: Figurementioning
confidence: 99%
“…This is apart from the inclusion (addition) of nanofillers (e.g., graphene) in thermosets which could serve as a means to improve the cross-linking process (catalyst-like effects during preparation/manufacturing), and to enhance the mechanical, physical and chemical properties of the final product. With that being said, the addition could also bring challenges related to morphology (issues relevant to polymer structure at the nano-and macro-scale), and agglomeration (issues relevant to dispersion or nanoparticles size) [8,9]. Such an influence on resin impregnation and polymerisation requires optimised control to acquire industrial processing windows for composites' manufacturing and characterisation.…”
Section: Introduction 1backgroundmentioning
confidence: 99%
“…To overcome this hurdle, PSAs have been admixed with ceramic fillers [10,11] to produce TC PSA films with thermal conductivity reaching 0.75 Wm -1 K -1 . Compared to ceramic fillers, carbon allotropes feature greater thermal conductivity because of sp 2 -hybridized carbon atoms through which electrons are delocalized [12]; thus, they have great potential for realizing PSAs with greater thermal conductivity. It has been reported that the thermal conductivity of the PSA containing 1 wt% reduced graphene oxide was 1.03 Wm -1 K -1 [9].…”
Section: Introductionmentioning
confidence: 99%